1992
DOI: 10.1515/cclm.1992.30.1.27
|View full text |Cite
|
Sign up to set email alerts
|

Sensitive Amplified Immunoenzymometric Assays (IEMA) for Human Insulin and Intact Proinsulin

Abstract: Summary:Immunoenzymometric assays (lEMAs) for human insulin and intact proinsulin were developed using the amplification system developed by Johannsson et al. (Clin. Chim. Acta 148 (1985) 119 -124) for the detection of the enzyme alkaline phosphatase. The detection limit of the assays was 0.8 pmol/1 for proinsulin and 0.8 pmol/1 for insulin whereas it was 1.8 pmol/1 and 2.3 pmol/1 respectively for the homologous immunoradiometric assays (IRMA). These assays are superior to immunoradiometric assays in terms of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
31
0

Year Published

1993
1993
2007
2007

Publication Types

Select...
10

Relationship

6
4

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 14 publications
(14 reference statements)
0
31
0
Order By: Relevance
“…Plasma glucose concentration was measured on a Hitachi 911 analyser (Hitachi, Tokyo, Japan) using the glucose oxidase method (intra and inter-batch CV <4%). Insulin concentration was measured using in-house DELFIA method [18]. The UK National External Quality Assessment Service (UKNEQAS) (Guildford Peptides, Guildford, UK) results showed that the CV was 12.5% at <45 pmol/l, 9.6% at 45-90 pmol/l and 4.3% at >90 pmol/l.…”
Section: Methodsmentioning
confidence: 99%
“…Plasma glucose concentration was measured on a Hitachi 911 analyser (Hitachi, Tokyo, Japan) using the glucose oxidase method (intra and inter-batch CV <4%). Insulin concentration was measured using in-house DELFIA method [18]. The UK National External Quality Assessment Service (UKNEQAS) (Guildford Peptides, Guildford, UK) results showed that the CV was 12.5% at <45 pmol/l, 9.6% at 45-90 pmol/l and 4.3% at >90 pmol/l.…”
Section: Methodsmentioning
confidence: 99%
“…Plasma glucose was measured by an automated hexokinase method, and plasma insulin, proinsulin, and split proinsulin were measured by two-site immunometric assays (7). Statistical methods.…”
Section: Methodsmentioning
confidence: 99%
“…All samples were permanently stored at Ϫ70°C within 4 h. Plasma glucose was measured in the routine National Health Service Laboratory at Addenbrooke's Hospital by the hexokinase method (24). Plasma insulin was measured by two-site immunometric assays with either 125 I or alkaline phosphatase labels (25,26). Cross-reactivity with intact proinsulin was Ͻ0.2% and interassay coefficients of variation were Ͻ7%.…”
Section: Methodsmentioning
confidence: 99%